Adiwiyata Program Reduced Activities in Training Mi Khadijah Students' Responsibility Skills in Malang City - Isnaini, Putri Karlia; Aziza, Imro'atul; Firdausyah, Siti Roudhotul; Ertanti, Devi Wahyu (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research focuses on analyzing the implementation of the Adiwiyata program, specifically the